2011
DOI: 10.1536/ihj.52.153
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Atrial Fibrillation on 30-Day Clinical Outcome in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: SummaryThis study evaluated the association between atrial fibrillation (AF) and 30-day clinical outcome in patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Between January 2005 and October 2009, 783 consecutive patients with acute STEMI undergoing primary PCI were enrolled. Of these patients, 85 (10.9%) with AF during admission were categorized into group 1, while the remaining 698 (89.1%) with sinus rhythm during admission ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…37) AF occurs in 6 to 11% of STEMI patients, and has been associated with increased in-hospital and long-term morality. [38][39][40][41] Recently, Batra, et al published a paper on the importance of AF in AMI patients, including STEMI and NSTEMI. 42) They found that irrespective of AF type, for example, new onset, paroxysmal, or chronic AF, AF patients suffered a higher rate of MACE compared to NSR, and there was no difference in the MACE rate between the types of AF.…”
Section: Discussionmentioning
confidence: 99%
“…37) AF occurs in 6 to 11% of STEMI patients, and has been associated with increased in-hospital and long-term morality. [38][39][40][41] Recently, Batra, et al published a paper on the importance of AF in AMI patients, including STEMI and NSTEMI. 42) They found that irrespective of AF type, for example, new onset, paroxysmal, or chronic AF, AF patients suffered a higher rate of MACE compared to NSR, and there was no difference in the MACE rate between the types of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the baseline characteristics and clinical outcomes of AF patients who underwent PCI [4][5][6][7][8]. However, there are few studies that relate to the second-generation DES era.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports revealed that 5-11 % of patients who undergo percutaneous coronary intervention (PCI) have concomitant AF [4][5][6]. AF has been associated with poorer in-hospital and long-term outcomes in patients with coronary artery disease (CAD) who underwent PCI in the bare-metal stent and first-generation drug-eluting stent (DES) eras, owing to their high risk of ischemic events [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In another recent prospective cohort study by Lin et al . [14] the AF population was frequently represented by females with history of diabetes, HT and stroke, extensive myocardial damage, higher Killip class (>3)and NYHA class, and low EF. Similarly, less of these patients had adequate postprocedural coronary perfusion flow rate (TIMI 3 flow rates 84.7% vs.93.7%, for AF and sinus rhythm groups, p=0.003).…”
Section: Incidence and Clinical Characteristics Of Af In Ami (Table 1)mentioning
confidence: 99%
“…In patients undergoing primary PCI, AF was not found to be an independent determinant of inpatient mortality, but remained a significant predictor of 30-day mortality [14, 16], 90-day outcomes [15] and 1-year mortality [4]. This could be partly attributable to the fact that better TIMI-3 flow rates were achieved using PCI and adjunct antithrombotic therapy, and the use of contemporary treatment with ACEIs [9,34], ARBs [11, 12], beta-blockers [36] and statins [37, 38] all of which have been shown to reduce the risk of AF development especially in patients with higher Killip, NYHA class and LV dysfunction.…”
Section: Prognostic Significance Of Af In Ami (Table 2)mentioning
confidence: 99%